The present situation of home blood pressure measurement among outpatients in Japan. (2nd January 2020) - Noda, Aoi; Obara, Taku; Abe, Shinya; Yoshimachi, Shoko; Satoh, Michihiro; Ishikuro, Mami; Hara, Azusa; Metoki, Hirohito; Mano, Nariyasu; Ohkubo, Takayoshi; Goto, Teruaki; Imai, Yutaka
ABSTRACT: Objective: To clarify the present situation of home blood pressure (HBP) measurement among Japanese patients. Methods: A nationwide questionnaire survey regarding HBP measurement was conducted on patients aged 20 years or older who had visited 20 community pharmacies to have their prescriptions filled. Results: In total, 76.7% of 1, 103 hypertensives and 40.9% of 1, 106 normotensives had their own devices for HBP measurement. Compared with normotensives, a higher proportion of hypertensives recognized the guideline-based reference values for HBP and clinic BP. Compared with hypertensives who did not have a physician's recommendation, those who did more often had their own devices, recognized the guideline-based reference values for HBP, and measured HBP every day (70.4%, 1.5%, and 31.6% vs. 91.1%, 6.9%, and 65.4%, respectively). Among 793 hypertensives who measured HBP, a higher proportion of those with a physician's recommendation measured HBP according to optimal guideline-based procedures compared with those without. Among 560 hypertensives who recorded HBP readings, a higher proportion of those with a physician's recommendation (74.6%) showed all HBP readings to their physicians compared with those without (35.3%). Conclusions: Our findings suggest that physicians should recommend measuring HBP in accordance with the Japanese Society of Hypertension guidelines more aggressively, and provide more detailed explanations to patients regarding how to measure HBP.